(untitled) (Research, Society and Development, 2020)
The primary purpose of this study was to examine the prevalence of burnout among university academicians in Ethiopia in relation with emotional intelligence and areas of work life factors. Descriptive survey study design, specifically cross-sectional survey was employed. 375 academic staffs were selected by using proportionate stratified random sampling method. Purposive sampling was followed to select 6 universities and two universities from each generation of universities. Maslach Burnout Inventory 22 items of Educators Survey, 28 items of the Areas of Work life Survey and 33 items of Brief Emotional Intelligence Scale (BEIS-10) were used to collect information from respondents. Relationship of variables with burnout was tested using Pearson correlation coefficients and two sample t-test. The findings of the present study showed that there was moderate level of burnout on the university academicians. Emotional intelligence have significant association at 0.01 and the association is positive and very strongly with burnout. Work area life has positive and very strong association with burnout level among university academic staff which is significant at 0.01 two tailed test. Finally the concerned bodies should consider different direction to prevent academicians from burnout and it is also recommended that administrators and the educationists utilize these findings to develop and improve teacher performance and prevent the on-set of burnout.